Pemberdayaan Usaha Mikro Kecil Dan Menengah Konveksi Hijab Melalui Modal Sosial Di Desa Candi Mulyo Kabupaten Jombang - risnawati risnawati; Mokhtar Sayyid; Rina Sulistyowati; Satriya Manggala Liastra (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
This community service activity aims to provide guidance to small, micro and medium enterprises of hijab convection in Candi Mulyo Village, Jombang Regency. The form of coaching is by providing assistance in the form of guidance on how to overcome capital and marketing problems through social capital in the era of the covid 19 pandemic. The evaluation of the success of this activity is to be able to identify social capital in the form of a familial method (sowan) to Islamic boarding schools in Jombang Regency from a marketing perspective. While the capital solution does not involve banking but uses the social capital method, offering it to friends who have capital to get capital by offering a profit-sharing system.